The cost-effectiveness of radiofrequency ablation for treating patients with gastric antral vascular ectasia refractory to first line endoscopic therapy. (2nd June 2020) - Magee, Cormac; Graham, David; Leonard, Catherine; McMaster, Jessica; Davies, Heather; Skotchko, Maria; Lovat, Laurence; Murray, Charles; Mealing, Stuart; Smart, Howard; Haidry, Rehan
Abstract: Objective: This economic evaluation aims to provide a preliminary assessment of the cost-effectiveness of radiofrequency ablation (RFA) compared with argon plasma coagulation (APC) when used to treat APC-refractory gastric antral vascular ectasia (GAVE) in symptomatic patients. Methods: A Markov model was constructed to undertake a cost-utility analysis for adults with persistent symptoms secondary to GAVE refractory to first line endoscopic therapy. The economic evaluation was conducted from a UK NHS and personal social services (PSS) perspective, with a 20-year time horizon, comparing RFA with APC. Patients transfer between health states defined by haemoglobin level. The clinical effectiveness data were sourced from expert opinion, resource use and costs were reflective of the UK NHS and benefits were quantified using Quality Adjusted Life Years (QALYs) with utility weights taken from the literature. The primary output was the Incremental Cost-Effectiveness Ratio (ICER), expressed as cost per QALY gained. Results: Over a lifetime time horizon, the base case ICER was £4840 per QALY gained with an 82.2% chance that RFA was cost-effective at a threshold of £20, 000 per QALY gained. The model estimated that implementing RFA would result in reductions in the need for intravenous iron, endoscopic intervention and requirement for blood transfusions by 27.1%, 32.3% and 36.5% respectively. Compared to APC, RFA was associated with an estimated 36.7% fewer procedures. Conclusions: RFA treatment is likely to be cost-effective for patients with ongoing symptoms following failure of first line therapy with APC and could lead to substantive reductions in health care resource.